ENHANCING STATISTICAL UNDERSTANDING THROUGH PjBL, VIRLENDA, AND WHATSAPP: A STUDY IN UNIVERSITAS PGRI ADI BUANA SURABAYA - Lydia Lia Prayitno; Ninik Mutianingsih (IAIN Ambon, 2021)
This study was motivated by the difficulties of students transforming the data into frequency tables and graphs and appreciate a group of data. This is envolve in low student understanding. Encounter this situation, researchers felt the need to carry out CAR to rise these problems through PjBL supported by Virlenda and Whatsapp due to the pandemic situation that did not allow offline learning. So, the purpose of this study is to enhance students' statistical understanding through PjBL supported by Virlenda and Whatsapp. The subject 10 students from the 2019-C class of mathematics education program, Universitas PGRI Adi Buana Surabaya. Data were collected through observation, documentation, and tests. The data were analyzed quantitatively and qualitatively. The indicators of this study are there is no statistical understanding of students in the category less than